The Role of Brain-Derived Neurotrophic Factor in Epileptogenesis: an Update - Wang, Xinyi; Hu, Zhe; Zhong, Kai (Frontiers in Pharmacology, 2021)
Epilepsy, which is characterized by spontaneous recurrent seizures, is one of the most common and serious chronic neurological diseases in the world. 30% patients failed to control seizures with multiple anti-seizure epileptic drugs, leading to serious outcomes. The pathogenesis of epilepsy is very complex and remains unclear. Brain-derived neurotrophic factor (BDNF), as a member of the neurotrophic factor family, is considered to play an important role in the survival, growth and differentiation of neurons during the development of the central nervous system. Recent years, a series of studies have reported that BDNF can maintain the function of the nervous system and promotes the regeneration of neurons after injury, which is believed to be closely related to epileptogenesis. However, two controversial views (BDNF inhibits or promotes epileptogenesis) still exist. Thus, this mini-review focuses on updating the new evidence of the role of BDNF in epileptogenesis and discussing the possibility of BDNF as an underlying target for the treatment of epilepsy.